2013
DOI: 10.1089/ars.2012.4863
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Chromatin Remodeling in Chronic Obstructive Pulmonary Disease and Smoking-Related Diseases

Abstract: Significance: Chronic obstructive pulmonary disease (COPD) is predominantly a tobacco smoke-triggered disease with features of chronic low-grade systemic inflammation and aging (inflammaging) of the lung associated with steroid resistance induced by cigarette smoke (CS)-mediated oxidative stress. Oxidative stress induces various kinase signaling pathways leading to chromatin modifications (histone acetylation/deacetylation and histone methylation/demethylation) in inflammation, senescence, and steroid resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
109
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(113 citation statements)
references
References 194 publications
3
109
0
1
Order By: Relevance
“…In addition, there may be other underlying mechanisms, such as oxidative stress. 25 Clinical and experimental studies have shown that the production of reactive oxygen species (ROS) is increased in COPD patients by inhalation of toxic substances, [26][27][28] and that the antioxidative system in these patients is impaired, 29 leading to a state of high oxidative stress. After such an increase in ROS production, the spillover of ROS from the lung could lead to systemically increased levels of oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there may be other underlying mechanisms, such as oxidative stress. 25 Clinical and experimental studies have shown that the production of reactive oxygen species (ROS) is increased in COPD patients by inhalation of toxic substances, [26][27][28] and that the antioxidative system in these patients is impaired, 29 leading to a state of high oxidative stress. After such an increase in ROS production, the spillover of ROS from the lung could lead to systemically increased levels of oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…Despite smoking increases the extent of OS [37,38] and may contribute to BPH risk, although not clearly [39], we did not exclude smokers because we wanted to compare the effects of D-004 and SP in conditions near to routine practice, in which smoking unfortunately this habit is common. The frequency of smokers was relatively high (12 of 48 randomized subjects, 25%), but similar in both groups, so that this factor had no impact on the comparative results.…”
Section: Discussionmentioning
confidence: 99%
“…Chromatin remodeling may be important for the repair of DNA damage in oxidative lesions, in order to maintain genome stability (65). Components of the chromatin remodeling multiprotein complexes may harbor develop gene sequence mutations that lead to protein inactivation or loss of expression in various types of human cancer, including ovarian clear cell carcinoma (66).…”
Section: Additional Biomarker Candidates In Ovarian Clear Cell Carcinomamentioning
confidence: 99%